Surgical Strategies for Fertility Preservation in Women with Cancer - A. Bedaiwy, Mohamed; Zanotti, Kristine; Y. Shahin, Ahmed; Yahya Abdel Rahman, Mohamed; W. Hurd, William (Current Women's Health Reviews, 2010)
Survival has significantly improved for women diagnosed with cancer during the reproductive years. The majority of these women will desire children after completion of their cancer therapy. Future fertility often is eliminated or impaired by surgical removal of reproductive organs for the treatment of gynecologic cancers or by radiation or chemotherapy for the treatment of other cancers. As a result, several strategies have been developed in an attempt to preserve fertility in these women, including alternate surgical approaches, protecting reproductive organs during treatment, and removing and storing oocytes prior to cancer treatment for future use. Surgical approaches used in women with early gynecologic cancers include unilateral oophorectomy for ovarian cancer, radical trachelectomy for cervical cancer, and progestin therapy to avoid surgery for endometrial cancer. Ovarian function and fertility can be preserved in women requiring pelvic irradiation by ovarian transposition away from the treatment field. In women requiring systemic chemotherapy, surgical removal of ovarian tissue followed by cryopreservation and subsequent transplantation after the patient is determined to be in remission has been shown to restore ovarian function and result in pregnancy. To provide the best chance of future fertility, these surgical approaches to fertility preservation must be implemented as part of the initial cancer therapy, prior to definitive radiation or chemotherapy.
Keywords: ovarian transplatation